Food intake and Physical activity of Hemodialysis Patient Undergoing Treatment at National Kidney Center, Kathmandu, Nepal - Baniya, Bhupal; Joshi, Hari Shankar; Regmi, Sanjeev; Dhungel, Kshitiz Upadhyay (Janaki Medical College Journal of Medical Science, 2017)
Background and Objectives: Nutrition has been an integral part of medical management in CKD patient in which total food and protein intake plays vital role in survival rate of patient. This study was done to investigate the nutritional status, food intake and physical activity level of hemodialysis patient for the period of three month in National Kidney center in Kathmandu. Materials and Methods: Quantitative descriptive method was applied for the collection of data from 80 patients undergoing hemodialysis in National kidney center, Kathmandu. The data so obtained was further analyzed by using SPSS 16 version software and Microsoft excel sheet. Discussion: The BMI result of sample population underdoing hemodialysis showed that 12% of them were underweight, 9% were overweight, 57% were in normal range and 1% were obese. Similarly 42.5% of sample population were involved in some kind of physical activity where as 57.5% of the patient were not involved in any sort of physical activity. On the other hand, 52.5% of MHD patient did not follow the instruction provided in food chart and only 47.5% patient consume food according to diet chart. Conclusion: The patient should be provided nutritional counseling before starting dialysis so that nutritional challenges could be reduced. As poor nutritional intake, Socio economic barrier, low physical activity level etc. are major problem of dialysis patient. Janaki Medical College Journal of Medical Sciences (2016) Vol. 4 (1): 33-40